A Clinical Study on the Utility of Muscle Biopsy in Patients with Suspected Myopathy - Sudhakar Karunakaran; Abraham Kuruvilla; Muralidharan Nair; Sruthi S Nair; Deepti Narasimhaiah (Annals of Indian Academy of Neurology)
Background and Objectives: The role of muscle biopsy needs to be redefined in an era where genetic studies have largely supplanted the need for a pathological diagnosis. The objective of the study was to evaluate the utility of muscle biopsy in suspected myopathies in terms of diagnostic confirmation and modifying therapy in a developing country. Methods: We conducted a retrospective observational study of patients who underwent muscle biopsy in our center between April 2017 and 2019. The diagnostic utility and therapeutic impact of muscle biopsy were assessed descriptively and using an ordinal score. We further analyzed the correlation of the pathological diagnosis with the genetic and immunological data. Results: Among the 70 patients included in the study over a 2-year period, 33 (47.1%) were aged 18 years or less and the mean age was 23.4 (±16.2) years. A specific diagnosis or diagnostic category could be established in 39 (55.7%) of all patients and 21 (63.6%) among pediatric patients by muscle biopsy. The most common categories were muscular dystrophies in 27 (38.6%) patients and inflammatory myopathies in seven (10%) patients. Mitochondrial myopathy was confirmed in two (2.9%), while three (4.3%) had other specific diagnosis and 31 (44.2%) had indeterminate/normal biopsy reports. Muscle biopsy confirmed the pre-biopsy diagnosis in 29 (41.4%) patients and changed the clinical diagnosis in 16 (22.9%) patients. Category-wise, the change in pre-biopsy diagnosis was significant only in suspected mitochondrial myopathies, but not in other categories. Conclusions: Muscle biopsy helped in securing a specific diagnosis in approximately one-half of the patients. This study underscores the enduring relevance of muscle biopsy in settings where resources for advanced genetic testing and data analysis are constrained.